Minat Mahasiswa Fakultas Ekonomi dan Bisnis UMSU Dalam Menggunakan Lembaga Keuangan Syariah - Delyana Rahmawany Pulungan (CERED Indonesia Institute, 2020)
This study uses a quantitative approach with associative research types. This research was conducted on students of Economics and Business Management, Muhammadiyah University of North Sumatra Semester 6 (six). The samples taken in this study were 100 people. Data collection techniques in this study using questionnaires, documentation and interviews with respondents. The results showed that financial literacy had a positive and significant effect on student interest in using Islamic financial institutions, inclusion had a positive and significant effect on student interest in using Islamic financial institutions. Simultaneously, financial literacy and financial inclusion have a positive and significant influence on student interest in using Islamic financial institution.